Pyrrolizidine alkaloids: occurrence, biology, and chemical synthesis - Robertson, J; Stevens, K (Royal Society of Chemistry, 2016)
This review covers the isolation and structure of new pyrrolizidines; pyrrolizidine biosynthesis; biological activity, including the occurrence of pyrrolizidines as toxic components or contaminants in foods and beverages; and formal and total syntheses of naturally-occurring pyrrolizidine alkaloids and closely related non-natural analogues.